2002
DOI: 10.1177/026988110201600405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intrahippocampal injection of GABAergic drugs on memory retention of passive avoidance learning in rats

Abstract: The effect of post-training intrahippocampal injection of gamma-aminobutyric acid (GABA) receptor agonists and antagonists, immediately after a training session on memory retention of passive avoidance learning in rats, was measured in the presence and absence of physostigmine. Post-training treatments were carried out in all the experiments. The different doses of the GABAA receptor agonist muscimol (2, 4 and 6 microg/rat) decreased memory retention in rats dose-dependently. The higher response was obtained w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
44
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 50 publications
9
44
0
Order By: Relevance
“…2). Overall, these data are consistent with previous reports demonstrating cognitive impairing effects of both baclofen and chlordiazepoxide on passive avoidance behavior (Swartzwelder et al, 1987;Castellano et al, 1989;Zarrindast et al, 2002). Furthermore, they exemplify the better side effect profile of GABA B receptor-positive modulators over that of full agonists and benzodiazepine anxiolytics.…”
Section: Discussionsupporting
confidence: 91%
“…2). Overall, these data are consistent with previous reports demonstrating cognitive impairing effects of both baclofen and chlordiazepoxide on passive avoidance behavior (Swartzwelder et al, 1987;Castellano et al, 1989;Zarrindast et al, 2002). Furthermore, they exemplify the better side effect profile of GABA B receptor-positive modulators over that of full agonists and benzodiazepine anxiolytics.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, infusion of bicuculline, a GABA A antagonist, decreased the memory-impairing effect of muscimol alone. This supports the conclusion that memory-impairing effects of muscimol occur through GABA A receptors (Zarrindast et al 2002). Other work demonstrates that intrahippocampal infusion of muscimol impaired one trial inhibitory avoidance when infused immediately but not more than 30 min after training (Rossato et al 2004).…”
supporting
confidence: 79%
“…For example, Zarrindast et al (2002) found that muscimol, a GABA A agonist, infused into the hippocampus after training in a passive avoidance task dose dependently decreased memory retention. Furthermore, infusion of bicuculline, a GABA A antagonist, decreased the memory-impairing effect of muscimol alone.…”
mentioning
confidence: 99%
“…Indiscriminant reduction in GABA A R-mediated inhibition by nonselective antagonists facilitates synaptic plasticity (Wigström and Gustafsson, 1983), increases vigilance (Ferraro et al, 1999), and improves memory performance (Zarrindast et al, 2002); however, these nonselective drugs have no therapeutic utility because of their proconvulsant and anxiogenic properties (Ben-Ari et al, 2007). Inverse agonists selective for ␣5GABA A Rs facilitate some forms of learning and enhance synaptic potentiation without a proconvulsant effect (Atack et al, 2006a).…”
Section: Discussionmentioning
confidence: 99%